Purification, Renaturation, and Stability Study of FlaA Protein - Li, Jiecheng; Jian, Xiaohong; Zhang, Zhi; Li, Zaixin (International Journal of Public Health and Medical Research, 2026)
Objective: To establish an efficient purification and renaturation process for Helicobacter pylori flagellin A (FlaA) and to investigate its storage stability. Methods: Recombinant Escherichia coli cells were disrupted by high-pressure homogenization. Inclusion bodies were purified by washing with Triton X-100 and low-concentration urea. Single-factor experiments were conducted to optimize initial protein concentration, pH, temperature, and the concentrations of glycine, arginine, and glycerol during dialysis renaturation. Furthermore, an ultrafiltration-dialysis combined renaturation process was established. The Bradford method was used to monitor protein concentration changes to evaluate storage stability. Results: High-pressure homogenization effectively disrupted bacterial cells. After purification, the purity of FlaA protein exceeded 90%. The optimal conditions for dialysis renaturation were 0.1 mol/L glycine and 0.3 mol/L arginine, yielding a renaturation recovery of 80.67%. The ultrafiltration-dialysis combined renaturation achieved a recovery of 75.32% while significantly reducing processing time. Storage at a protein concentration of 0.5 mg/mL resulted in the slowest degradation rate at low temperature. Conclusion: This study establishes an efficient and economical process for the purification and renaturation of FlaA inclusion bodies, providing technical support for the large-scale preparation of anti-H. pylori egg yolk antibodies.